(untitled) (Pesquisa Odontológica Brasileira, 2000)
The aim of this study was to evaluate the effect of powder processing and sintering conditions on the resultant porosity of hydroxyapatite, which was calculated as percentage of the theoretical density of hydroxyapatite. The parameters evaluated were the effect of load during uniaxial pressing, the initial size of the particles of hydroxyapatite, and sintering temperature and time. There was an inverse correlation between load and porosity, and between sintering temperature and porosity, but there was no correlation between sintering time and porosity. An increase in the size of the particles resulted in greater porosity. It was concluded that a combination of loading conditions and sintering temperature can provide hydroxyapatite with a wide range of porosities.